Agent technologies and web engineering applications and systems - Alkhatib, Ghazi, 1947-; Rine, David C. (Advances in information technology and web engineering series., 2009)
"This book presents various applications of the growing perspective of agent technologies as they apply the web engineering"--Provided by publisher.